Study of Eimeria necatrix in broiler chicken from Aurangabad District of Maharashtra state India - Jadhav, B N; Nikam, S V; Bhamre, S N; Jaid, E L (International Multidisciplinary Research Journal, 2011)
The objective of this study was first to investigate the prevalence of poultry coccidiosis and to identify the coccidial species occurring in the study area on local strain .The study involvedÂ Â survey, fecal examination, and identification of coccidial species based on their morphology, predilection site in the intestine and sporulation time. During the present study ten species of Eimeria are found in Broiler chicken. Seven species are redescribed and three are new species.Â Â